Language of dissent: a discourse analysis of protest poetry in contemporary Indonesia - Gerry Kadamehang (Indonesian Journal of Politics and Literary Studies, 2026)
Background: In post-Reformasi Indonesia, protest poetry has re-emerged as a key medium for articulating dissent, collective emotion, and political critique amid democratic regression. Objective: This study examines how contemporary protest poetry constructs resistance, negotiates power, and articulates collective identity and memory. Method: A qualitative approach integrates Critical Discourse Analysis, poetic–stylistic analysis, and sociolinguistic analysis across printed, digital, and performative texts. Results: Protest poetry functions as counter-discourse through delegitimizing representations of the state, while poetic devices such as metaphor and repetition enable affective political critique; non-standard language and grassroots registers further construct collective identity and preserve social memory. Implication: These findings highlight protest poetry as a vital site of political meaning-making and cultural resistance in contemporary Indonesia. Novelty: This study offers an integrative analytical framework that bridges discourse analysis, poetics, and sociolinguistics to reveal how aesthetic forms operate as political strategies in contemporary protest movements.